2017
DOI: 10.1021/acs.energyfuels.6b02817
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Coke Quality Variation between Heat-Recovery and Byproduct Cokemaking Technology

Abstract: Coke structural properties that lead to coke quality difference between heat recovery and byproduct cokemaking technology are investigated. Coke fingers collected from two zones (bottom center and top center) of a commercial heat recovery oven were analyzed and compared to the coke produced from the same coal blend using a moveable-wall slot oven. Coke fingers were studied at set intervals, starting from the floor of the heat recovery oven through the top of the bed, and from the slot oven wall to wall. Coke s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Each oven has a different design, resulting in different heating rates during the plastic stage of coking [4]. The heating rate during the formation of the plastic layer influences the development of the resulting coke microstructure [4, 17] and microtexture [18]. The difference in confining pressure also has an impact on coke microstructure development [7], and the combination of these parameters influence the coke strength after reaction (CSR) value of the coke generated [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each oven has a different design, resulting in different heating rates during the plastic stage of coking [4]. The heating rate during the formation of the plastic layer influences the development of the resulting coke microstructure [4, 17] and microtexture [18]. The difference in confining pressure also has an impact on coke microstructure development [7], and the combination of these parameters influence the coke strength after reaction (CSR) value of the coke generated [4].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies in the literature have demonstrated that their laboratory-scale ovens are able to produce replicate cokes to those generated in pilot-scale ovens, with the CSR of the cokes produced matching (within measurement error) their pilot-scale counterparts [13, 5]. Other studies echo the common knowledge that the CSR of a coke is strongly dependent on coking conditions [4, 18], and suggest that given the dependence of heating rate on coke oven design, it is not straightforward to produce a small-scale coke with an analogous CSR to the equivalent pilot-scale coke.…”
Section: Introductionmentioning
confidence: 99%